Molecular Mechanics Studies on Chamazulene - SATHYANARAYANAMOORTHI, V.; MAHALAKSHMI, S. (Asian Journal of Chemistry, 2010)
The molecular mechanics studies have been undertaken to identify the presence of stable conformers. The attached methyl and ethyl groups are rotated one by one for various dihedral angles and minimum conformational energy of the molecule is recorded. Various parameters such as compression energy, bending energy, torsional energy and van der Waal’s energy of the molecule are recorded. The final steric energy and related thermodynamic quantity are found. The heat of formation and related strain energy are also noted.